The evolution of ecosystem services: A time series and discourse-centered analysis - Chaudhary, Sunita; McGregor, Andrew; Houston, Donna; Chettri, Nakul (Environmental science & policy, 2015)
•We analyze the history of ecosystem services as a discourse and track its evolution over time.•Ecosystem services emerged from ecology and economics in the US to rapidly become a globally significant discourse.•Four key moments are identified where ideas and initiatives from academia and policy became institutionalized.•There is a need and opportunity for other disciplines, particularly from the social sciences, to influence the next phase of institutionalization. The concept of ecosystem services is becoming increasingly influential in environmental research and policy – reshaping human–environment interactions. In this paper, we trace the rapid growth of ecosystem services across academic disciplines and amongst organizations at the boundary of science and policy. We approach ecosystem services as an evolving discourse and track its evolution across key institutional time frames. The review shows how the concept emerged in the United States as an economic and ecological response to ecosystem degradation, and has since expanded to incorporate a wide array of disciplinary perspectives across multiple countries. A discursive-institutional analysis identifies four key moments when ideas and initiatives from academia and policy became institutionalized. Using a spiral metaphor, we argue such moments shape subsequent research, policy and practice. The foundations of economics and ecology remain dominant, however there are emerging opportunities for other disciplines who have been marginal to this discourse up until now to contribute to what is becoming an increasingly powerful and global concept. We argue that social scientists must become more involved to ensure issues of poverty, justice, equality, differentiated wellbeing, governance, rights, and marginality are to influence the next institutional spiral of this important and influential discourse.